“Antes da linguagem, há o silêncio”: espaço, memória e exílio em Rabo de foguete: os anos de exílio, de Ferreira Gullar. - PINHO, Thaisa Viegas de (2022)
This study starts from the relationship between the character Ferreira Gullar and the exile space in the work Rabo de Foguete: Anos de Exílio (2010) during the period of the Military Dictatorship that was installed in Brazil in the years of 1964. The character/narrator moves through different spaces (Russia, Chile, Argentina) to escape the political persecution of his country and experiences as a witness who saw the horrors of repression and survived them. Unable to return to their place of belonging, Gullar becomes a clandestine in foreign lands, experience a life in anonymity, whose destiny becomes increasingly uncertain and insecure. Through this research, we seek to understand how the character in Rabo de Foguete relates with the environment, from the abrupt separation of his place of origin to the spaces traveled during exile. Furthermore, the memory of repression revisited through written testimony, the complex relationship of literature with trauma. We will base our methodology on a bibliographic research, focused on the study of experience of Yi-Fu Tuan in Espaço e lugar: a perspectiva da experiência (2013), Eric Dardel with the study O homem e a terra: a natureza da realidade geográfica (2015), Edward W. Said Reflexões sobre o exílio e outros ensaios (2003), Alexis Nouss in Pensar o exílio e a migração hoje (2020) Miriam L. Volpe Geografias de exílio (2005), Márcio Seligmann-Silva O local do testemunho (2010), Elio Gaspari in A Ditadura Derrotada (2014); Tempo passado: cultura da memória e guinada subjetiva (2007), in Beatriz Sarlo and Rosane Batista in Ferreira Gullar: memórias do exílio (2014).